Efficiency of preprocessing methods for discrimination of anatomically similar pine species by NIR spectroscopy - AKDENİZ, ESRA (My University, 2023)
Identification of wood species with fast, reliable and non-destructive methods is highly important for forestry and wood-related industries. Near-infrared spectra of anatomically similar pine species (Pinus sylvestris L. and Pinus nigra J.F. Arnold) were taken and analysed by partial least squared discriminant analysis (PLS-DA) for comparing the efficiency of preprocessing methods. Raw data were subjected to multiple scatter correction (MSC), standard normal variate (SNV), Savitzky–Golay for derivatives (1st and 2nd Dr) and smoothing (Sm) and combination of these preprocessing methods (1st Dr, 1st Dr + SNV, 1st Dr + MSC, Sm + 1st Dr and Sm + 2nd Dr). The success of the models was determined by the accuracies of test sets that did not participate in the calibration phase. In this study, it was determined that not all the preprocessing methods improve the model performance. Smoothing with 1st derivatives (Sm + 1st Dr) enhanced 14.3% improvement and have the best performance (95%) for classification of pine species. For understanding modelled relationship, mean spectra and selectivity ratio were used. It was found that discrimination was held by the differences at their absorption, and the most important variables for wood classification were noted around 4000–7000 cm−1.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Near-infrared spectroscopy; wood identification; discrimination; preprocessing methods; classification; PLS-DA; NEAR-INFRARED SPECTROSCOPY; ARTIFICIAL NEURAL-NETWORKS; LEAST-SQUARES REGRESSION; COMPARATIVE WOOD ANATOMY; NONDESTRUCTIVE ESTIMATION; SWIETENIA-MACROPHYLLA; PRINCIPAL COMPONENT; MICROFIBRIL ANGLE; RAPID PREDICTION; MACHINE VISION; Near-infrared spectroscopy; wood identification; discrimination; preprocessing methods; classification; PLS-DA